The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/emph/eot022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for independent evolution of functional progesterone withdrawal in primates and guinea pigs

Abstract: Humans and guinea pigs differ from other mammals by maintaining high progesterone levels in pregnancy all the way through birth. Here we investigated the evolutionary history of this condition and conclude that it evolved independently in the human and the guinea pig lineages. Furthermore we investigated the gene expression during cervical re-modelling and found only a small number of gene regulatory events that seem to be common between humans and guinea pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
1
17
0
2
Order By: Relevance
“…These findings in 2 rodent species and a variety of strains, as well as in women (15), indicate that structural changes in the stroma, i.e., reduced cell nuclei density and degradation of cross-linked collagen while progesterone in circulation is elevated, occur well before the uterus develops contractile capabilities for labor at term (62). The apparent withdrawal of progesterone efficacy in rodents and humans for cervix ripening, does not contradict clear evidence that the decline in serum progesterone is likely to be important for labor in rodents and other species compared to sustained high concentrations in circulation in primates throughout pregnancy (81,82). Perhaps the more important insight from these studies in rodents and from early reviews of cervix remodeling in women is that the ripening phase occurs well before term and is distinct from the dilation phase, which is associated with dilatability in response to labor.…”
Section: Ripeningmentioning
confidence: 99%
“…These findings in 2 rodent species and a variety of strains, as well as in women (15), indicate that structural changes in the stroma, i.e., reduced cell nuclei density and degradation of cross-linked collagen while progesterone in circulation is elevated, occur well before the uterus develops contractile capabilities for labor at term (62). The apparent withdrawal of progesterone efficacy in rodents and humans for cervix ripening, does not contradict clear evidence that the decline in serum progesterone is likely to be important for labor in rodents and other species compared to sustained high concentrations in circulation in primates throughout pregnancy (81,82). Perhaps the more important insight from these studies in rodents and from early reviews of cervix remodeling in women is that the ripening phase occurs well before term and is distinct from the dilation phase, which is associated with dilatability in response to labor.…”
Section: Ripeningmentioning
confidence: 99%
“…The detailed mechanisms of birth in guinea pig are not well understood. However, recent work on cervix found expression of P4-metabolizing enzymes in term cervix, suggesting that the shift toward proinflammatory activity of birth is triggered by potentially independently evolved local P4 withdrawal (Nnamani et al 2013). Notably, local withdrawal also appears to be the main mechanism in sheep, which, like primates, experience the luteal -placental shift, but also show overt P4 withdrawal at term.…”
Section: What Can Animals Reveal About Human Pregnancy and Parturitiomentioning
confidence: 99%
“…Extending the limited knowledge in various species of these mechanisms, occurring regardless of the decrease of systemic P4, is a promising future avenue. As suggested by Nnamani et al (2013) for the guinea pig, preliminary insights can be attained via transcriptomic analyses.…”
Section: What Can Animals Reveal About Human Pregnancy and Parturitiomentioning
confidence: 99%
“…In primates, the source of progesterone shifts from the ovaries to the placenta in early pregnancy, and high progesterone levels are maintained throughout gestation (Haluska et al, 1997). Importantly, progesterone production by the placenta does not decline prior to birth in Catarrhine primates (Nnamani et al, 2013). Instead the fall in progesterone action is said to be functional involving local mechanisms such as target tissue metabolism and changing progesterone receptor expression and function (Zakar and Mesiano, 2011).…”
Section: Guinea Pig Model Of Human Labor and Preterm Birthmentioning
confidence: 99%
“…In agreement with these processes, progesterone administration can prolong pregnancy beyond term in rodents, but not in humans (see below) or higher non-human primates. Using Laurasiatheria species as the outgroup of Euarchontoglires it was suggested that the common ancestor of primates and rodents gave birth after systemic progesterone withdrawal and the functional withdrawal mechanism evolved later in the primates (Nnamani et al, 2013). The disparate mechanisms of progesterone maintenance and withdrawal in the two clades are underpinned by differences in cellular and molecular regulation, which limits the usefulness of common laboratory rats and mice in modeling parturition in the human (Mitchell and Taggart, 2009).…”
Section: Guinea Pig Model Of Human Labor and Preterm Birthmentioning
confidence: 99%